Simultaneous determination of aflatoxins and ochratoxin A in single and mixed spices - Wan Mustapha, Wan Ainiza; Selamat, Jinap; Sanny, Maimunah (Elsevier, 2015)
Methods for the extraction and high performance liquid chromatography (HPLC) quantification of aflatoxins (AFs) and ochratoxin A (OTA), in a single procedure, from selected individual spices, i.e., coriander, chili, cumin, fennel and turmeric, were developed. The optimized method was then applied to spice mixtures, i.e., curry, kurma and soup powders. The aflatoxins B1, B2, G1 and G2 (AFB1, AFB2, AFG2 and AFG2) and ochratoxin A were extracted using a multi-mycotoxin immunoaffinity column, and the determination was conducted using reverse-phase HPLC and fluorescence detector (FLD) with a photochemical derivatisation system. The samples, for recovery study, were spiked with 3 different concentrations of AFB1 and AFG1 (0.4, 4.0 and 40 μg/kg), AFB2 and AFG2 (0.2, 2.0 and 20 μg/kg), and OTA (0.5, 5.0 and 50 μg/kg). Validation was conducted to confirm that the method was suitable for multi-toxin and multi-matrix analysis. The recoveries of AFB1, AFB2, AFG1 and AFG2 ranged from 72% to 100% for coriander, chili, cumin and all of the spice mixtures, and lower recoveries, ranging from 61% to 80%, were attained for fennel and turmeric. The recovery of OTA ranged from 96% to 113% for coriander and from 73% to 100% for chili, cumin, fennel, turmeric and all of the spice mixtures. The repeatability (RSDr) of the determination of AFB1, AFB2, AFG1, AFG2 and OTA contained in all of the spices ranged from 2% to 19%, whereas the LOD was 0.1 μg/kg for AFB1/AFG1, 0.05 μg/kg for AFB2/AFG2 and 0.1 μg/kg for OTA, and the LOQ was 0.4 μg/kg for AFB1/AFG1, 0.2 μg/kg for AFB2/AFG2 and 0.5 μg/kg for OTA. The results indicated that the method for the simultaneous determination of AFs and OTA can be applied to both single and mixed spices and is suitable for routine laboratory analysis.